MicroRNA-146a in rheumatoid arthritis: a new therapeutic strategy - Pauley, Kaleb M (Immunotherapy, 2011)
MiR-146a has been shown to play an important role in the negative regulation of inflammatory innate immune responses, and to be differentially expressed in a number of human diseases including rheumatoid arthritis (RA). However, evidence for the potential therapeutic use of miR-146a in human disease has been lacking. The current paper demonstrates the potential therapeutic application of miR-146a for RA by demonstrating the inhibitory effect of miR-146a on osteoclastogenesis in vitro. Moreover, using a collagen-induced arthritis mouse model, they were able to demonstrate that intravenous administration of double stranded miR-146a resulted in the suppression of cartilage and bone destruction, despite relatively unaffected immune cell infiltration of the synovium and inflammatory cytokine expression.